Soils Derived from Ophiolitic Rocks in Northeastern Leyte: Morphological, Physical, and Chemical Properties - Quiñones, Cecille Marie O.; Asio, Victor B. (Annals of Tropical Research, 2015)
Soils that developed from ophiolitic rocks in Leyte, Philippines are relatively unknown. Seven soil profiles were studied at various slope positions in Basper watershed underlain by ophiolitic rock to evaluate the soil morphological, physical-hydrological, and chemical properties. Results show that the soils range from poorly to moderately developed and from shallow to deep soils. The soil profile development appears to be related to the slope positions. Those on the footslope and summit positions had thinner solum while those in the lower backslope developed into deep soils. In addition, the soils are generally clay loam to sandy clay loam in the upper horizon. They tend to be sandy in the lower section of the profile due to the saprolite coming from the ophiolitic parent rock. Physical-hydrological properties such as bulk density values increase with depth which is accompanied by a decrease in total porosity while saturated hydraulic conductivity of surface soils are higher than that in the subsurface soils. In terms of chemical properties, soil pH values vary from 5.9 to 7.10 indicating near neutral soil reaction. Available P, soil organic carbon, total N, as well as the exhangeable K and Na are generally low. Effective CEC measures of the soils range from 10.61 to 25.81 cmol kg.